2009
DOI: 10.1590/s0100-39842009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Medidas do tendão do calcâneo no primeiro ano de vida

Abstract: OBJECTIVE: To determine the thickness and width of the calcaneal tendon (Achilles tendon) in both male and female, eutrophic children at 2, 6, 9 and 12 months of age. MATERIALS AND METHODS: The present prospective and descriptive study included 38 boys and 31 girls. Measurements of the tendons were performed by means of ultrasonography, with a linear, 14-MHz probe, at the level of the medial malleolus. RESULTS: Tendon thicknesses observed in the boys were 2.4 mm, 2.3 mm, 2.4 mm, and 2.4 mm, respectively at 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…With respect to the morphometric study of the Achilles tendon and its possible relation with familial hypercholesterolemia, and therefore increased risk for cardiovascular diseases, the study developed by Bezerra et al (8) , "Measurements of the calcaneal tendon in the first year of life", published in the present issue, justifies the research in the absence of normality curves by age, weight, length and gender in the childhood, which in many occasions, makes the early diagnosis of some diseases more difficult. The authors report that "No study was found in the literature that have measured thickness and width of the calcaneal tendon in children up to 12 months of age" and, in fact, as usual in the academic community, little research has been dedicated for defining normality standards and variations, emphasizing the investigation of the diseases, particularly in our specialty.…”
Section: Editorialmentioning
confidence: 99%
“…With respect to the morphometric study of the Achilles tendon and its possible relation with familial hypercholesterolemia, and therefore increased risk for cardiovascular diseases, the study developed by Bezerra et al (8) , "Measurements of the calcaneal tendon in the first year of life", published in the present issue, justifies the research in the absence of normality curves by age, weight, length and gender in the childhood, which in many occasions, makes the early diagnosis of some diseases more difficult. The authors report that "No study was found in the literature that have measured thickness and width of the calcaneal tendon in children up to 12 months of age" and, in fact, as usual in the academic community, little research has been dedicated for defining normality standards and variations, emphasizing the investigation of the diseases, particularly in our specialty.…”
Section: Editorialmentioning
confidence: 99%